Neuromuscular electrical stimulation-enhanced rehabilitation is associated with not only motor but also somatosensory cortical plasticity in chronic stroke patients: an interventional study - Syoichi Tashiro; Katsuhiro Mizuno; Michiyuki Kawakami; Osamu Takahashi; Takuya Nakamura; Mabu Suda; Koshiro Haruyama; Yohei Otaka; Tetsuya Tsuji; Meigen Liu (SAGE Publishing, 2019)
Background: Somatosensory function has been frequently overlooked in clinics and research in the field of chronic stroke. The effects of neurorehabilitation interventions on sensory processing have still to be investigated using electrophysiological means. This study investigated the effect of hybrid assistive neuromuscular dynamic stimulation (HANDS) therapy utilizing closed-loop electromyography-controlled neuromuscular electrical stimulation (NMES), on sensory changes and cortical plasticity among patients with chronic stroke. Methods: This study was a prespecified analysis of 23 participants involved in an ongoing large interventional study. Patients with severe upper limb hemiplegia dues to chronic stroke underwent 3 weeks of inpatient HANDS therapy, where daily treatment consisted of 8 h of NMES combined with wrist splinting, 90 min of comprehensive occupational therapy, and the practice of bimanual activities of daily living. Somatosensory evoked potentials (SEPs) and functional sensory assessments, including the Semmes-Weinstein monofilament test (SWMT) and thumb localizing test (TLT), were compared pre and post-treatment. Results: While no significant recovery of tactile sensation was observed, significant improvements in proprioception and motor function were induced. The number of cortical peaks significantly increased in the median nerve, but not in the tibial nerve. A total of 9 out of 11 participants who initially lacked certain peaks responded to treatment. Further analysis revealed a significant improvement in latency and amplitude of SEP peaks. Conclusions: Our results suggest that NMES-based neurorehabilitation induces certain plastic changes in the primary sensory cortex and in cortices associated with sensorimotor processing in people with chronic stroke sequelae, which may explain the observed improvements in proprioception.